Enhancement the performance of wire cutting process by additives nanopowder alumina (Al2O3) - Abed, Farook Nehad (2021)
Wire Electrical Discharge Machining (WEDM) is a non-traditional thermal machining process used to manufacture irregularly profiled parts. WEDM includes high rates of cutting and superior quality in improving machining performance onto hard materials. Today the electric wire machine plays an important role in manufacturing a solar cell, which is the main goal in the clean world; the improvement of the performance of this machine required a new idea for that. So this problem can be solved by following the unique approach of machining wire electro discharge process through the additives of nanopowder to the dielectric solution so that the computers controlled wire-electrical discharge machining processes performance be directly dependent upon spark energy (spark gap voltage and peak current). This research mainly focuses on WEDM (Ti6242) titanium alloys using two different dielectrics, a regular dielectric and a Nanopowder dielectric (Al2O3) up to (2g/l) was selected as the main parameter.In contrast, coat brass wire was used as an electrode. Three response variables, such as material removal rate (MRR), recast layer (RL), and surface roughness (SR), was modeled using the response surface methodology in the WEDM process. The experimental design is based on the design of Box-Behnken. Six parameters were used in this study, namely, peak current, Ip 10A to 12A, pulse on time of 120 to 130μs, pulse off time of 50 to 60μs, the voltage at 20 to 50 V, wire feed 1 to 5 m/min and tensions 1 to 5 kg. The optimization of multi-response through desirability has optimized these reactions. ANOVA was used to identify the importance of the model developed. The testing results confirm the validity and appropriateness of the existing RSM model developed. In the case of machinability, the optimal parametric setting for the optimization process has been designed. A micro model was also developed to predict the recast layer, the substance removal rate, and surface roughness. The current research's primary focus is on studying the working surface's integrity after machining using dielectric Nanopowder WEDM. Nano (AL2O3) is the best option in the WEDM machining of Ti-6242. Experimental findings show that the lowest SR value is 1.39µm at the Ip=10A, Pon= 130µm, and Spv=20v with nanopowder in a dielectric improvement. Due to deionized water decomposition, machined samples and wire material were formed in free or compound form. Simultaneously, there was an improvement on the surface in Nanopowder used in dielectric by (2g/l) under the same operating conditions of the machine..